Assessing Quality of Food Products Using Electronic Noses: A Systematic Review - V. A. Binson; Sania Thomas (Proceedings)
In the global food industry, companies face various challenges, including the need for innovation to keep up with competition, expanding into new markets, and satisfying the ever-changing demands of consumers [...]